#TITLE_ALTERNATIVE# - YUDHA SWARA (NIM 23106025), MUHAMMAD
Gears are one of the most common parts that are used to transmit power and torque due to gear tooth contact mechanism. With this mechanism, no slip is expected during power transmission. In spite of that, gears defect can occur in some period of time. Gear defect can affect another part of machine to be damaged, for example bearing and shaft. This defect caused by many factors, such as manufacture and assembly error. Those errors can lead unique vibration spectrum characteristics to be occurred, which is sideband frequencies. The appearance of those frequencies usually followed by their harmonics, hence the vibration spectrum will be difficult to analyze. These difficulties will enhance if stepped spur gear is applied. To make the data easier to represent, another analysis can be used, called vibration cepstrum analysis. In this research, vibration cepstrum has been applied to detect gears vibration. Besides that it will also discuss about the characteristics and the source of vibration in gears system including the simulation of those characteristics using MatLab 7.0.4 software. After that, FRF and linear spectrum experiment are done. Then the acquired experiment data will be processed and analyzed. The acquired data shows that cepstrum vibration analysis can be performed if there are a lot of harmonic sideband frequency occurs. Thus, quefrency data become easier to interpret.